2003
DOI: 10.1007/s00284-002-3878-3
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cell Hydrophobicity in the Formation of Aerobic Granules

Abstract: Cell hydrophobicity is an important affinity force in cell self-immobilization and attachment processes. The role of cell hydrophobicity in the formation of aerobic granules has not been clear. Therefore, two series of experiments were conducted to investigate the role of cell hydrophobicity in the formation of aerobic heterotrophic and nitrifying granules in sequencing batch reactors, while the effects of shear strength, hydraulic selection pressure, and organic loading rate on the cell hydrophobicity were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
38
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(40 citation statements)
references
References 16 publications
2
38
0
Order By: Relevance
“…In this study, the cell surface hydrophobicity rates slightly increased with the incubation time from approximately 0.5% to 8.5% Ϯ 5.5% and 8.3% Ϯ 4.6% for C 16 and C 24 cultures, respectively, compared to approximately 4% in the control without any hydrocarbon. In contrast, the hydrophobicity rate in C 36 cultures could be as high as 23.9% Ϯ 3.7% (Fig.…”
mentioning
confidence: 85%
See 4 more Smart Citations
“…In this study, the cell surface hydrophobicity rates slightly increased with the incubation time from approximately 0.5% to 8.5% Ϯ 5.5% and 8.3% Ϯ 4.6% for C 16 and C 24 cultures, respectively, compared to approximately 4% in the control without any hydrocarbon. In contrast, the hydrophobicity rate in C 36 cultures could be as high as 23.9% Ϯ 3.7% (Fig.…”
mentioning
confidence: 85%
“…S1 in the supplemental material); this finding suggested that shorter alkanes resulted in a higher emulsifying activity, which allowed cells to access alkanes more easily. The C 16 , C 24 , and C 36 culture broths yielded 95.7, 25.4, and 15.8 mg liter Ϫ1 of crude biosurfactant, respectively. Among them, 2 glycolipid compounds (16-A and 16-B) (Fig.…”
mentioning
confidence: 99%
See 3 more Smart Citations